2011
DOI: 10.2527/jas.2010-3014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting daily water intake on cattle finished in feedlots

Abstract: the World Wide Web at:The online version of this article, along with updated information and services, is located on www.asas.org by Rodrigo Arias on November 15, 2011 jas.fass.org Downloaded from ABSTRACT: Records from 7 studies conducted during 1999 to 2005 were utilized to assess the effects of environmental factors on daily water intake (DWI) of finishing cattle. Data from unshaded feedlot pens (up to 24 pens utilized per study; 6 to 9 animals·pen −1 ) containing predominantly Angus crossbred cattle were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(134 citation statements)
references
References 21 publications
9
122
2
1
Order By: Relevance
“…The values 18.52L/day -20.39L/day were within the range of 15.1 -71.9litres for growing and finishing cattle [17] . The low water intake by all the breeds could have been as a result of environmental temperature (21 -27 o C) since water intake by animals is highly influenced by environmental temperature and season [18] . Although the water intake was low, it had no effect the feed intake as well as the weight gains and the general performance of all the breeds.…”
Section: Performancementioning
confidence: 99%
“…The values 18.52L/day -20.39L/day were within the range of 15.1 -71.9litres for growing and finishing cattle [17] . The low water intake by all the breeds could have been as a result of environmental temperature (21 -27 o C) since water intake by animals is highly influenced by environmental temperature and season [18] . Although the water intake was low, it had no effect the feed intake as well as the weight gains and the general performance of all the breeds.…”
Section: Performancementioning
confidence: 99%
“…Brosh et al (1998) indicated that there was an interaction between ME and SR that overall resulted in an increase in daily water intake. Arias and Mader (2011) reported that feedlot cattle finished in the summer consumed 87.3 % more (P < 0.01) water compared to cattle finished during winter (32.4 L/d versus 17.3 L/d). Additionally Arias and Mader (2011) indicated that thermal exchange is often impeded during heat wave events where adequate water supplies are unavailable.…”
Section: Water Requirementmentioning
confidence: 99%
“…Arias and Mader (2011) reported that feedlot cattle finished in the summer consumed 87.3 % more (P < 0.01) water compared to cattle finished during winter (32.4 L/d versus 17.3 L/d). Additionally Arias and Mader (2011) indicated that thermal exchange is often impeded during heat wave events where adequate water supplies are unavailable. Parker et al (2000) concluded that increased water consumption during summer can be attributed to the thermoregulatory mechanisms evoked to regulate core body temperature.…”
Section: Water Requirementmentioning
confidence: 99%
See 2 more Smart Citations